Contribution of the Zubair source rocks to the generation and expulsion of oil to the reservoirs of the Mesopotamian Basin, Southern Iraq - Al-Khafaji, Amer Jassim; Sadooni, Fadhil; Hindi, Mohammed Hadi (Petroleum science and technology, 2019)
The huge quantities of oil and gas reserved in the fields of southern Iraq must be matched by enough source rocks that can generate and expel equivalent amounts of hydrocarbons. This study is an attempt to evaluate the potential and efficiency of the Zubair Formation strata as potential source rocks that contributed to the hydrocarbon budget. A Multiproxy investigation including TOC, pyrolysis, palynofacies, carbon isotope and biomarker analysis were used to investigate such possibility. Results indicate that Zubair rocks were ranging from poor to excellent source rocks, early to moderate maturity, and generated and expelled much hydrocarbons to the Cretaceous reservoirs of the Basin.